Longitudinal Effect of Surface Treatments Modified by NaOCl-Induced Deproteinization and Nd:YAG Laser on Dentin Permeability - Machado Silva Esteves, Stella Renata [UNESP]; Rocha Lima Huhtala, Maria Filomena [UNESP]; Martins Gomes, Ana Paula [UNESP]; Ye, Qiang; Spencer, Paulette; De Paiva Goncalves, Sergio Eduardo [UNESP] (Mary Ann Liebert, Inc, 2016)
Objective: The purpose of this study was to evaluate dentin permeability after dentin hypersensitivity treatments: fluoride, adhesive system, and collagen deproteinization with andwithout Nd:YAGlaser exposure, and after erosive and abrasive challenges. Materials and methods: Dentin permeability was assessed by measuring dentinal fluid flow using a permeability device. Eighty bovine dentin specimens (6 mm diameter/1 mm thickness) had permeability measured in the presence of the smear layer and after removal of the smear layer by ethylenediaminetetraacetic acid (EDTA). They were then divided into eight groups according to treatment (n = 10): Group C, control; Group L, Nd:YAG laser; Group F, fluoride; Group FL, fluoride plus Nd:YAG laser; Group A, adhesive; Group AL, adhesive plus Nd:YAG laser; Group D, 10% NaOCl plus adhesive; and group DL, NaOCl plus adhesive plus Nd:YAG laser. Nd:YAG laser was irradiated at 60 mJ/pulse/10Hz/47.7 J/cm(2)/1 W and applied freehanded without contact for 60 sec. Permeability was measured 24 h after the treatments. The specimens were exposed to erosive and abrasive challenges for 5 days. Erosive challenge was done by immersion in Coca-Cola, four times a day/90 sec each. After the first and last erosive challenge of the day, the abrasive challenge was conducted by brushing the specimens (24,000 cycles/3.8 cm range/200 g weight), and permeability was measured again. Results were analyzed statistically using two factor ANOVA and Tukey tests (alpha = 0.05). Results: With the exception of groups FL and A, all treatments reduced permeability. A significant reduction in permeability was seen when the treatments were combined with laser exposure. The association of adhesive and Nd: YAG laser led to the lowest rate of permeability after 24 h. NaOCl-induced deproteinization associated with Nd:YAGlaser showed the lowest permeability rate after erosive/abrasive challenges. Conclusions: Dentin hypersensitivity treatments reduced dentin permeability when associated with Nd:YAG laser, even after erosive/abrasive challenges.